Regional Economic Convergence and Spatial Spillovers in Turkey - Ahmet Kýndap; Tayyar Dogan (International Econometric Review (IER), 2019)
Using sigma and beta convergence methods, this study tests economic convergence in Turkish NUTS-2 regions between 2004-2011. The findings of sigma convergence analysis show that the interregional income gap decreases during economic recession periods and increases during economic expansion periods. The beta convergence results obtained by the cross-sectional and panel estimations indicate the existence of absolute convergence. In addition, spatial data analysis provides strong evidence for the existence of spatial autocorrelation in regional income distribution.
Keywords: R11; R12; 330; Regional Disparity; Convergence; Spatial Autocorrelation; Spatial Econometrics; Spatial Spillovers